2014
DOI: 10.19070/2332-287x-1400015
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Cases in Manipal, South India: An Autopsy Study

Abstract: Considering these facts, and keeping in view the magnitude of this problem and absence of any recent data, an attempt has been made in the present study to make a complete and thorough analysis of suicides in terms of various epidemiological features,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
(64 reference statements)
2
1
0
Order By: Relevance
“…Out of the 356 cases, most victims, 277(77.80%), belong to the nuclear family, while the 79(22.19%) cases belong to the joint family (Table 3). Similar findings were observed in other studies [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Type Of Familysupporting
confidence: 92%
See 1 more Smart Citation
“…Out of the 356 cases, most victims, 277(77.80%), belong to the nuclear family, while the 79(22.19%) cases belong to the joint family (Table 3). Similar findings were observed in other studies [10][11][12][13][14][15][16][17][18][19][20].…”
Section: Type Of Familysupporting
confidence: 92%
“…However, Sharija et al [16] reported chronic alcoholism In our study, out of a total of 356 hanging cases, 290(82%) cases belong to the Hindu religion, while 55(15%) cases were Muslims (Figure 7). Studies conducted by Shetty [20]. we reported similar findings.…”
Section: Type Of Familysupporting
confidence: 84%
“…7 1 % a n d d r o w n i n g , 7 . 1 4 % ) a n d Manipal [22] (poisoning,31%;hanging,26%; firearm,16% and burns,11%). The presence of various poisons, ligature materials (such as rope, dupatta, etc.)…”
Section: Pattern Of Suicidal Deathsmentioning
confidence: 99%